EFFECT OF MALELO SANDAL SALT WITH HN03 TO THE EFFICIENCY OF CRYSTAL IMPLEMENTATION - Siti Sulastri; Susila Kristianingrum; Retno Arianingrum (Jurnal Penelitian Saintek, 2004)
The  objective   of  this  study   was  to  investigate    the  effect  of  soaking nitrate  acid  of Malelo  sand  to adsorption   efficiency   of chromium  (Cr). The Malelo  sand  was prepared   by soaking   in nitric  acid with variation of  concentration     were   17,5:  35  and   70%  for    24  hours   at  room temperature.    The  adsorption   efficiency   of  chromium   was  determined based  on concentration    of chromium   residue   after  adsorption.   which measured  using Atomic Absorption  Spectrophotometer    (AAS). The characterization    of Malelo  sand  determined   using  FTIR  and XRD.  The result  indicated  that the mean  ofadsorption    efficiency   of chromium  on Malelo   sand   without   preparation    and  soaking   in  nitrate   acid  with variation   concentration    17.5:  35 and  70%  were  91,36:  92,40:  92,72 and 94,004%  respectively.